Changes in water flows and water productivity upon vegetation regeneration on degraded hillslopes in northern Ethiopia: a water balance modelling exercise - Descheemaeker, Katrien K.; Raes, Dirk; Nyssen, Jan; Poesen, J.; Haile, M.; Deckers, J. (Commonwealth Scientific and Industrial Research Organisation, 2009)
The establishment of exclosures (i.e. areas closed for grazing and agriculture) is a common practice to reverse land degradation through vegetation regeneration in the semiarid highland areas of northern Ethiopia. In order to assess the effect of exclosures on water flows, the water balance components for different vegetation regeneration stages were assessed through field measurements and modelling. Successful model calibration and validation was done based on soil water content measurements conducted during 2 years in 22 experimental plots. In the protected areas, vegetation regeneration leads to an increase in infiltration and transpiration and a more productive use of water for biomass production. In areas where additional lateral water (runon) infiltrates, source–sink systems are created. Here, up to 30% of the annual rainfall percolates through the root-zone towards the groundwater table. Increased biomass production in exclosures leads to possibilities for wood harvesting and cut and carry of grasses for livestock feeding. Together with water conservation and more productive use of water, the latter contributes to increased livestock water productivity. At the landscape scale, the creation of vegetation filters, capturing resources like water and nutrients, reinforces the rehabilitation process and healthy landscape functioning.